2018
DOI: 10.17236/sat00168
|View full text |Cite
|
Sign up to set email alerts
|

Wild boar and infectious diseases: evaluation of the current risk to human and domestic animal health in Switzerland: A review

Abstract: The Eurasian wild boar is widely distributed in Europe and hunting bags reveal a massive increase in the population. Since wild boar and domestic pigs are susceptible to the same pathogens and can infect each other, free-ranging wild boar populations are increasingly considered to be a threat to the pig industry. Switzerland has an outstanding veterinary health situation due to its official free-of-disease status for many diseases, and the role that wildlife could play as a source of infection for domestic ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 61 publications
0
33
0
1
Order By: Relevance
“…Free-living wild boars are recognized as a potential viral disease reservoir for pathogens from domestic pigs [29, 30]. In Japan, wild boars have increased significantly in population size and distribution range [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Free-living wild boars are recognized as a potential viral disease reservoir for pathogens from domestic pigs [29, 30]. In Japan, wild boars have increased significantly in population size and distribution range [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…The rapid expansion of wild boar presence represents a special risk for pasture pigs due to an increase in the frequency of potential contacts. Undesirable mating among domestic and wild pigs and the potential contamination with shared pathogens are the most common threats [78,79]. Wild boars have not only been reported as playing an important role in the transmission of parasites, bacteria, and viruses to domestic animals but also to humans [80][81][82][83].…”
Section: Wild Boarmentioning
confidence: 99%
“…Wild boars have not only been reported as playing an important role in the transmission of parasites, bacteria, and viruses to domestic animals but also to humans [80][81][82][83]. These animals have been identified as potential sources of African swine fever virus [56,73,84], Aujeszky's disease [78,79], brucellosis [78,79,82], Campylobacter [80], classical swine fever [85], giardiasis [80], salmonellosis [81], Streptococcus suis [77], toxoplasmosis [81,82], trichinellosis [61,82], tuberculosis [86,87], and yersiniosis [81] in domestic animals, and leptospirosis, tuberculosis, hepatitis E, brucellosis, and trichinellosis in humans [56,78,83]. Conversely, Batista Linhares et al indicated greater probability of contagion of enzootic pneumonia caused by Mycoplasma hyopneumoniae from domestic pigs to wild boars [88].…”
Section: Wild Boarmentioning
confidence: 99%
See 1 more Smart Citation
“…Konieczne jest równocześnie utrzymanie jak najmniejszej gęstości populacji dzików na danym terenie. Dla osiągnięcia powyższego celu konieczny jest odstrzał dzików na poziomie około 70% pierwotnej populacji dzików/ rok (9).…”
Section: Artykuł Przeglądowy Reviewunclassified